2010
DOI: 10.4034/1519.0501.2010.0102.0016
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Clínica dos Selantes Realizados com Cimento de Ionômero de Vidro Modificado por Resina (Vitremer) em Molares Decíduos

Abstract: Cárie dentária; Selantes de fossas e fi ssuras; Denti ção decídua. Dental caries; Pit and fi ssure sealants; Denti ti on primary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Researchers indicate that the appearance of caries on sealed teeth can be attributed to problems such as inadequate isolation of the operative field, excessive masticatory force and inadequate patient compliance [6,14]. In the present study, the presence of caries was identified thirty-six months after sealant application, which may have been due to an incorrect initial diagnosis at the time of selection, since the morphology of the irregular occlusal surface favors plaque retention and the development of caries in both permanent and primary teeth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers indicate that the appearance of caries on sealed teeth can be attributed to problems such as inadequate isolation of the operative field, excessive masticatory force and inadequate patient compliance [6,14]. In the present study, the presence of caries was identified thirty-six months after sealant application, which may have been due to an incorrect initial diagnosis at the time of selection, since the morphology of the irregular occlusal surface favors plaque retention and the development of caries in both permanent and primary teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, occlusal surfaces are highly susceptible to the development of dental caries due to their specific anatomical shape, which includes grooves and pits that facilitate the accumulation of food remnants and provide a favorable niche for caries. This situation is further aggravated by the difficulty to brush this region, due to the poor motor skills found in children [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations